Brand Personality As A Predictor Of Consumer Brand Relationship - Keni Keni; Verena Sandra Esmeralda (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The main idea of this paper is to investigate three dimensions of brand personality, which are excitement, sincerity and ruggedness to predict CBR constructs which comprise brand love, brand trust and brand loyalty. A convenience sampling method was utilized, in which the respondents are one of soft drink brand’s consumers based in Jakarta. All data were then gathered through an online survey. In total, 312 participants responded to the survey. Structural equation modelling (SEM), specifically partial least square (PLS) was employed to analyze the data. The results of the data analysis indicate that sincerity, excitement and ruggedness brand personality serve as the positive and significant predictors towards brand trust, brand love and brand loyalty. Both the theoretical and practical contributions are discussed in this study.